Research and Design of Mobile Client and Web Application Based on WebRTC Technology - Hong Lin; Song Wang; Xin Yang; Bin Fu (Dianxin kexue)
WebRTC technology has some good characteristics of open and standardized, simple and extendable, open sourced and free. The Web applications can be easily and quickly developed by calling the Web API which are provided by WebRTC technology and being standardized. Besides, the mobile clients and applications of real-time audiovisual communications with high quality can also be developed by fully exploiting the WebRTC core implementation library. The main technical features of WebRTC technology were summarized. Based on the summary, the technical analysis was given about how to design and develop the mobile client application and Web application based on WebRTC technology. The reference design and the implementation of the mobile clients applications, the Web application and the service platform which supports these two kinds of the applications were provided.